O iconostasis paulistano (Igrejas Orientais em São Paulo: mediação da multiplicidade - 1950-2011) - Katz, Felipe Beltran (2012)
This work tries to point out the diversity of the oriental Christianity in Sao Paulo, through the oriental churches. These institutions are connected to the immigrant communities that came to Sao Paulo since the 19th century until the mid 20th century. Amongst the oriental Christians that have come to the city are Arabs, Armenians, Greeks, Russians and Ukrainians. These communities are divided in twelve different churches, that are located in different areas of the city. The research is based on the collected testimony of each clergy member of each church, some oriental Christians from Sao Paulo and bibliography that studies the historical experience of these institutions in other parts of the world. Far from being something completely strict, presenting Rites and peculiarities of ancient Christianity, the oriental churches of Sao Paulo are inserted in the daily life of the metropolis. These churches try to mediate their past, while maintaining the faith and culture of immigrant groups with their current situation in the city. A situation where the 1st generation of immigrants is diminishing trough age and the migratory flux is not being renewed. The oriental churches, according to the testimony of clerics and faithful, are experiencing a reflexive moment in their course in the metropolis. However, this work does not try to judge which church best preserves it‟s past, but understand that they are part of the daily life of the city. They are oriental churches from Sao Paulo, therefore, their situation permeates appropriations that best respond their experience in Sao Paulo